Oscillatory motion of an electrically conducting viscoelastic fluid over a stretching sheet in a saturated porous medium with suction/blowing. (27th March 2006) - Rajagopal Rajagopal, K. K.; Veena Veena, P. H. P. H.; Pravin Pravin, V. K. V. K.
Abstract : The effect of an oscillatory motion of a viscoelastic fluid over an infinite stretching sheet through porous media in the presence of magnetic field with applied suction has been studied. The surface absorbs the fluid in a porous medium in the presence of magnetic field and the velocity oscillates depending on the stretching rate ( b ) . Analytical expressions for the velocity and the coefficient of skin friction have been studied, first by the perturbation method and then by power series method. The effect of viscoelastic parameter k 1, porous parameter k 2, magnetic parameter Mn, and the vertical distance x in the presence of suction/blowing on the velocity and the flow characteristics are discussed. The velocity of the viscoelastic fluid is found to decrease in the presence of magnetic field and porous media, as compared to the study of viscous fluid. It is also found that the effect of unsteadiness in the wall velocity and skin friction are found to be appreciable in the presence of suction/blowing parameter.